Nuevos horizontes en la traducción e interpretación de Max Weber? una entrevista con Joaquín Abellán - Bodart, Cristiano das Neves (Latitude, 2025)
The interview with Joaquín Abellán, professor at the Complutense University of Madrid and a prominent translator of Max Weber into Spanish, analyzes common errors in traditional translations of Weber’s texts, especially in Latin America. Abellán emphasizes the need for philological revisions based on the critical edition (Max Weber Gesamtausgabe), highlighting conceptual issues that distort Weber’s thought. He criticizes, for example, the translation of Beruf as “vocation” and Herrschaft as “domination,” and questions the usual interpretation of “plebiscitary democracy” as an authoritarian form of government. According to him, Weber was referring to transformations in modern political parties, not to personalist regimes. The interview also addresses Marianne Weber’s role in the posthumous edition of Economy and Society, the international reception of Weber’s work, and the influence of Talcott Parsons. Abellán proposes more faithful translations and defends a critical, precise, and contextualized reading of Weber, contributing to a renewal of Weberian studies.